Disasters and their impact on violence against women: A correlational analysis for the Peruvian case 2014 – 2021 - Héctor Javier Bendezú Jiménez; Luis Enrique Felix Arcibia (Revista de Estudios Latinoamericanos sobre Reducción del Riesgo de Desastres, 2024)
This research analyzes two problems in Peru. On the one hand, disasters and extreme events (i.e., landslides, low temperatures, floods, droughts, mudslides, avalanches, heavy rains, among others) that directly impact the most vulnerable populations and, on the other, the violence that women suffer (rape and femicides), mainly adolescents and girls. The econometric analysis of Ordinary Least Squares (OLS) is applied to two variables, one of proxy characteristics made up of the record of femicide and the number of cases of sexual violence against women, and the other of emergencies caused by disasters for the period 2014-2021. The correlation between these variables, taken from official sources in Peru, was analyzed, verifying a positive trend relationship between sexual violence against women and the number of disasters. That is, as the number of disasters increases, regardless of the number of disasters type, the cases of rapes against women increase. Unfortunately, this relationship is just as positive with respect to the increase in the number of femicides in Peru in the period analyzed.